Heavy Metal Contamination in Water and Sediments of Passur River near the Sundarbans Mangrove of Bangladesh (Journal of Environmental Science and Natural Resources, 2017)
The study was conducted to investigate the heavy metal contamination in water, sediment and fishes from the Passur river in the Mongla port area near Sundarbans mangrove during the period from January to June 2013. The water samples were collected from five different sampling stations as St-1 (upstream- 1km upper from port area), St-2 (port area), St-3 (downstream-1km lower from port area), St-4 (tributary) and St-5 (1 km lower from tributary). Sediment samples were collected monthly from Station-1, 2 and 3 during the study period. The concentrations of heavy metals (Cu, Zn, Fe and Cr) in water were found from water much lower than the permissible level. The concentrations of five heavy metals (Cr, Cu, Ni, Pb and Fe) in the sediment samples were Fe at 23481.61 to 15339.4 mg/kg, while other metals were much lower and found little difference among different months. The result indicated that passerious pollution in the Passur river is due to heavy metals; whereas the concentrations of elements found could mainly be attributed to geological sources. To maintain the sound environment and healthy ecosystem of the river and the surrounding areas, need proper management and monitoring of water quality of the river.J. Environ. Sci. & Natural Resources, 10(1): 15-19 2017